2010
DOI: 10.1152/ajpcell.00068.2010
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic upregulation of arginase II in human lung endothelial cells

Abstract: Activated arginase has been implicated in many diseases including cancer, immune cell dysfunction, infections, and vascular disease. Enhanced arginase activity has been reported in lungs of patients with pulmonary artery hypertension. We used hypoxia as a model for pulmonary hypertension and studied the effect of exposure to hypoxia on arginase activity in human lung microvascular endothelial cells (HMVEC). Hypoxia induces upregulation of arginase activity as well as mRNA and protein levels of arginase II (Arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
67
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 55 publications
8
67
3
Order By: Relevance
“…This present study conWrms those Wndings and extends this observation to show and upregulation in aging cardiac tissue, more speciWcally cardiac myocytes. This is consistent with the upregulation and increased expression of Arg-II in old endothelial cells (Krotova et al 2010) and endothelial cells exposed to and atherogenic stimulus (Ryoo et al 2008(Ryoo et al , 2011Santhanam et al 2008) and may contribute to NOS uncoupling or the production of peroxinitrate. This in turn will lead to a change in the nitroso-redox milieu of the cell (Berkowitz 2007;Kim et al 2009a).…”
Section: Discussionsupporting
confidence: 84%
“…This present study conWrms those Wndings and extends this observation to show and upregulation in aging cardiac tissue, more speciWcally cardiac myocytes. This is consistent with the upregulation and increased expression of Arg-II in old endothelial cells (Krotova et al 2010) and endothelial cells exposed to and atherogenic stimulus (Ryoo et al 2008(Ryoo et al , 2011Santhanam et al 2008) and may contribute to NOS uncoupling or the production of peroxinitrate. This in turn will lead to a change in the nitroso-redox milieu of the cell (Berkowitz 2007;Kim et al 2009a).…”
Section: Discussionsupporting
confidence: 84%
“…This finding is consistent with recent work in human lung endothelial cells, where arginase inhibition using small molecule inhibitors completely prevented hypoxiainduced cellular proliferation [7]. Recently, Krotova et al [27] found that silencing HIF-2 in lung endothelial cells prevented hypoxia-induced arginase II expression. Similarly, Takeda et al [28] found that in thioglycollate-elicited mouse peritoneal macrophages arginase II was induced by Th2 mediated HIF-2 activation.…”
Section: Discussionsupporting
confidence: 91%
“…Increased metabolism of L-arginine by enhanced arginase II activity in the endothelium has been shown to contribute to the reduced L-arginine and NO levels (Morris et al, 2003;Xu et al, 2004). In addition, hypoxia, which is a major contributor in COPDrelated pulmonary hypertension, upregulates arginase in human lung microvascular endothelial cells (Krotova et al, 2010). Our data suggest that COPD-associated pulmonary hypertension can effectively be targeted by inhalation of arginase inhibitors.…”
Section: Discussionmentioning
confidence: 64%